Can emphysema influence size discrepancy between radiologic and pathologic size measurement in subsolid lung adenocarcinomas? - Lim, Jae‐Kwang (Thorac Cancer, 2019)
BACKGROUND: To investigate the difference in the measured diameter of subsolid lung adenocarcinomas of thin‐section computed tomography (TSCT) and pathology according to presence of emphysema. METHODS: A total of 268 surgically resected pathologic T1 or T2 adenocarcinomas visualized as subsolid nodules (SSNs) on TSCT were analyzed in 252 patients. Two observers measured the greatest diameters of the whole tumor (WTsize) and solid tumor (STsize) on TSCT in lung windows, classified nodules as part‐solid or nonsolid, and recorded the presence of regional emphysema. Interobserver variability was determined with intraclass correlation coefficients (ICC). CT measurements were compared to pathologic size (Psize) and invasive size (PIsize) using the Wilcoxon signed‐rank test. RESULTS: The interobserver agreement between the diameters measured by the two observers was strong for WTsize (ICC = 0.968 [95% confidence interval, 0.960–0.975]) and STsize (ICC = 0.966 [95% CI, 0.950–0.969]). Radiologic WTsize was significantly greater than Psize (P < 0.001), while STsize was less than PIsize. The WTsize of the emphysema group was better correlated with Psize than WTsize of the normal lung group (P = 0.001), while the STsize of the normal lung group was better correlated with PIsize than STsize of the emphysema group. The concordance rate in T staging between CT and pathologic analysis was better correlated in patients with normal lungs than in those with emphysema (P = 0.023). CONCLUSION: STsize on TSCT was underestimated in patients with emphysema, resulting in higher discordance in T staging between TSCT and pathologic analysis for subsolid lung adenocarcinomas.